Plastic-film-side seeding, as an alternative to traditional film mulching, improves yield stability and income in maize production in semi-arid regions - Bing-chao ZHANG; Han HU; Zheng-yu GUO; Shuai GONG; Si SHEN; Shu-hua LIAO; Xin WANG; Shun-li ZHOU; Zhong-dong ZHANG (Journal of Integrative Agriculture, 2023)
Planting under plastic-film mulches is widely used in spring maize production in arid-cold regions for water conservation and warming the soil. To ameliorate the associated issues such as plastic-film residues and additional labor during the “seedling release” in spring maize production, we have developed a plastic-film-side seeding (PSS) technology with the supporting machinery. In the semi-arid regions of Northwest China, a 7-year trial demonstrated that PSS increased plant number per hectare by 6 547 and maize yield by 1 686 kg ha–1 compared with the traditional method of seeding under plastic-film mulch (PM). Two-year experiments were conducted in two semi-arid regions to further understand the effects of PSS on three important aspects of production: (i) the moisture and temperature of soil, (ii) maize development, yield output, and water use efficiency (WUE), and (iii) the revenue and plastic-film residuals in comparison with that of flat planting (CK) and PM. Continuous monitoring of the soil status demonstrated that, compared with CK, the PSS treatment significantly increased the temperature and moisture of the 0–20 cm soil in the seeding row at the early stage of maize development, and it also promoted grain yield (at 884–1 089 kg ha–1) and WUE, achieving a similar effect as the PM treatment. Economically, the labor inputs of PSS were equal to CK, whereas the PM cost an additional 960 CNY ha–1 in labor for releasing the seedlings from below the film. Overall, the PSS system increased profits by 5.83% (547 CNY ha–1 yr–1) and 8.16% (748 CNY ha–1 yr–1) compared with CK and PM, respectively. Environmentally, PSS achieved a residual film recovery rate of nearly 100% and eliminated 96 to 130 kg ha–1 of residual plastic-film in PM in 3–5 years of maize production. Collectively, these results show that PSS is an eco-friendly technique for improving yield stability and incomes for the sustainable production of maize in semi-arid regions.